Analisis Implementasi Pendidikan Moral Pancasila Sebagai Upaya Pencegahan Bulliying di Sekolah - Eri Susanto (Cendikia: Jurnal Pendidikan dan Pengajaran, 2023)
This research aims to analyse the implementation of Pancasila moral education as an effort to prevent bullying in schools. This research uses a qualitative methodology, combining an extensive literature review from various sources, including traditional print media and electronic sources such as books and online journals. I did a search using Google Scholar to find scientific articles relevant to the topics